Performance of Cordyceps militaris Mutant Regarding Anti-cancer Agent Cordycepin Production in Submerged Culture Obtained by Ion Beam Irradiation - Das, S.K.; Masuda, M.; Hatashita, M.; Sakurai, A.; Sakakibara, M. (Our Nature, 2010)
Performance of Cordyceps militaris mutant obtained by high-energy ion beam irradiation regarding anti-cancer agent cordycepin production in submerged culture was investigated. It was established that the mutant renders a higher production performance in surface liquid culture, needs to observe its performance in submerged culture. Two kinds of media were used for submerged culture comprising a basal medium and the optimized media for C. militaris mutant and control (wild strain) each. HPLC analysis for cordycepin concentration, mutarotase GOD (glucose oxidase) method using Glucose CII test for glucose concentration, pH meter for pH were measured. Analysis showed that the cordycepin production of mutant in submerged culture using basal medium was 2.82 times (181.77%) higher that of the control; whereas, in optimized media, the production of control was 9.06 times (806.25%) higher than that of the mutant. In contrast, the cordycepin productions of this mutant in submerged culture were suppressed to about 80% and 3% relative to the surface liquid culture; whereas, those controls were about 30% and 80% using basal and optimized media, respectively. Glucose consumption was faster in all cases of the control in both basal and optimized media with a higher mycelial growth, and interestingly, it was extremely slow in case of mutant in optimized medium. The pH analysis showed that as the production was increasing, the pH value also increasing towards the neutral (pH= 7) in all the cases of mutant and control, except in case of mutant using optimized medium in which the pH value remained more or less static accompanied by a lower production. These results suggested that the prospective mutant had a poor performance in submerged culture using optimized media, but had a better performance in basal medium, although the production in basal medium is too low to be taken into consideration as a commercial point of view. Stress furnished by shaking may be one of the major explainable causes of decreased production here. It my also be assumed that with a lower concentrations of C and N sources, this mutant is better tolerable to shear stress. Therefore, it is suggested to use surface liquid culture rather than the submerged one to attain the highest production performance to be used for industrial uses. Key words: Production performance, Cordyceps militaris mutant, submerged culture, anticancer agent production DOI: 10.3126/on.v7i1.2547 Our Nature (2009) 7:1-9